Didactic model of information and communication competence formation of future specialists of economic - Kononets, Nataliia; Baliuk, Victoria; Zhamardiy, Valeriy; Petrenko, Lesya; Pomaz, Yuliia; Kravtsova, Nadiya; Shkola, Olena (My University, 2021)
In the higher economics education faces a principally new task – the creation of an integrative model of formation of future specialists in economics, who possess the skills of using the information andcommunication technologies, operating in a digital economy as well as displaying professional mobility. Therefore, the context of digital transformation of the Ukrainian society calls for the improvement of professional training of future specialists of economic profile in the university educational environment; their personal and professional formation and creation of information and communication competence acquires special importance. The authors have revealed and experimentally tested the effectiveness of the didactic conditions of the formation of information and communication competence of future economic professionals in the educational environment of the university: 1) creation of electronic educational resources; 2) introduction of the training studio «Digital technologies in the work of an economist»; 3) complex pedagogical influence by means of coaching. The didactic model of formation of information and communication competence of future economists in the educational environment of the university is developed and scientifically substantiated, as incorporating the following structural blocks: motivational-target, informationcontent, operational-effective and diagnostic-effective. It is experimentally proven that the implementation of certain didactic conditions has positively affected the effectiveness of the formation of information and communication competence of future economic professionals in the educational environment of the university
Didactic model of information and communication competence formation of future specialists of economic // N. Kononets, V. Baliuk, V. Zhamardiy, L. Petrenko, Yu. Pomaz, N. Kravtsova, O. Shkola // Journal for Educators, Teachers and Trainers, 2021. – Vol. – 12(4). – P. 170–181.
Keywords: модель, інформаційно-комунікаційна компетентність, умови, ресурсне навчання; model, information and communication competence, conditions, resource-based learning